(untitled) (Texas Journal of Medical Science, 2026)
Acute myocarditis (OM) is an inflammatory disease caused by various infections, with viruses being the most widespread pathogenic factor [1, 2]. The pathophysiology of OM can be based on direct infection caused by a viral infection, inflammatory reactions after infection, or a combination of both.